Extratos secos do rizoma de Kava-kava (Piper methysticum G. Forst) - avaliação da qualidade, toxicidade aguda, atividades biológicas e biodisponibilidade de kavaína - Juliana Veloso Ferreira (2019)
The dry root extract of the plant Piper methysticum G. Forst, popularly known as Kava-kava, has been widely marketed in Brazil due to its anxiolytic and sedative properties. Although the plant consumption in natura or present in herbal medicines is widely diffused, there is no complete monograph in official compendium and the available literature related to Kava-kava is scarce. In the present work, a fast and efficient analytical method was developed and validated, using high performance liquid chromatography with diode array detection, for the simultaneous quantification of the plant’s active markers (kavalactones: methysticin, dihydromethysticin, kavain, dihydrokavain, yangonin and desmethoxyyangonin) present in Kava-kava extract samples from compounding pharmacies. The quality control of these samples was performed through visual evaluation, assay and loss on drying. Quantitative analysis of the extracts showed a high variability in the individual and total contents of kavalactones between the samples. Kavain’s pharmacokinetic parameters were determined, after per os administration of the standard and the extract in mice, through a bioanalytical method, using liquid chromatography tandem mass spectrometry, developed and validated for the quantification of this marker in plasma samples. Through the obtained pharmacokinetic parameters, the relative bioavailabilty of kavain isolated and present in the extract was determined and the occurrence of pharmacokinetic synergism between this marker and other compounds present in the plant extract was demonstrated. Kava-kava extracts acute toxicity was evaluated after per os administration in rats and the extract could be classified as low acute toxicity. Kidney and liver histological analysis of animals treated with the extract indicated absence of acute toxicity in these organs. Regarding other evaluated biological activities, no antibacterial activity was observed for the extracts in in vitro models. Some of the extracts presented antifungal activity against Cryptococcus spp, however, the values obtained were not enough to continue the tests in in vivo models. Since kavain did not show such activity, it is assumed that it might be related to other compounds present in the extract. Antinociceptive activity of different Kava-kava extracts and kavain standard was confirmed through induced heat model in mice, two hours after per os administration. Through rotarod test, it was proved that the observed antinociceptive effect is not related to the impairment of the animal’s motor response after the treatment. The obtained results demonstrate the importance of effective quality control for Kava-kava extracts, to ensure its therapeutic efficacy and safety during use. Thus, the present work adds important information to the scientific literature regarding the activity, pharmacokinetics and composition of Kava-kava extract.